MANAJEMEN RECORD NEWS MAGAZINE TRAFFIC LIBRARY METRO TV - Sudiar, Nining (Jurnal Ilmu Budaya, 2013)
Record management of news magazine on traffic library on Metro TV is to handle audiovisual collections. Titis activity was started since audiovisual media was accepted in production ( master on air ) which is placed in storage ( traffic library), then it is ready to be reused by those who broadcast it. The record management of news magazine audiovisual collection traffic library Metro TV is good. The classification system on storage is made based on the needs of the institution to simplify the information retrieval. To support that, traffic library uses automatic system which can be accessed ( intranet). Anyhow, it is found the inappropriate storage capacity and the problem with vims. For that reason anticipation is needed by having new additional features such as statistic data and blocking the overlim.it users.